2011
DOI: 10.3382/ps.2010-01249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stunning current and frequency on meat quality, plasma parameters, and glycolytic potential in broilers

Abstract: This study was designed to determine the effect of electrical stunning variables (low currents and high frequencies) on meat quality, glycolytic potential, and blood parameters in broilers. A total of 54 broilers were stunned with 9 electrical stunning methods for 18 s using sinusoidal alternating currents combining 3 current levels (35 V, 47 mA; 50 V, 67 mA; and 65 V, 86 mA) with 3 frequencies (160, 400, and 1,000 Hz). Samples for meat quality were obtained from the pectoralis major (PM) and musculus iliofibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 30 publications
3
30
1
3
Order By: Relevance
“…In general, plasma CORT can be regarded as an indicator of stress conditions in chickens (Bedanova et al 2007;Haensch et al 2009;Xu et al 2011) as it has been shown to increase in transport-stressed broilers (Freeman et al 1984;Kannan et al 1997). In the present study, the concentrations of plasma CORT in the TWFR group was significantly lower (P < 0.05) than other two groups, indicating that water-misting sprays with forced ventilation can alleviate stress by transportation during high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In general, plasma CORT can be regarded as an indicator of stress conditions in chickens (Bedanova et al 2007;Haensch et al 2009;Xu et al 2011) as it has been shown to increase in transport-stressed broilers (Freeman et al 1984;Kannan et al 1997). In the present study, the concentrations of plasma CORT in the TWFR group was significantly lower (P < 0.05) than other two groups, indicating that water-misting sprays with forced ventilation can alleviate stress by transportation during high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…At 72 h postmortem, the muscles were dried and weighed (W 1 ), and then heated in a water bath at 85°C for 20 min (end-point temperature of 80°C), cooled in running water to ambient temperature, and then dried and reweighed (W 2 ). Cooking loss was evaluated as (%) = (W 1 − W 2 )/W 1 × 100% (Xu et al, 2011).…”
Section: Measurementsmentioning
confidence: 99%
“…Glycogen concentration of Pectoralis major decreased in carcasses stunned with high frequencies showing a fast exhaustion of glycogen at the early post mortem examination, according to Xu et al (2011). Preliminary results of the study showed that the use of lower intensity and frequency electrical conditions led to a major muscle glycogen reserve in Lot A carcasses than Lot control (Lot C 0.770 μL/50mL; Lot A 1.497 μL/50mL).…”
Section: Discussionmentioning
confidence: 90%
“…High stunning frequencies may improve meat quality without aggregating stress, when the current is not too low, with a considerable commercial advantage (Xu et al , 2011). Incidence of birds with carcass defects sufficient to cause downgrading or rejection, was generally low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation